Tax rates, tax socialization, and tax compliance of MSMEs: Patriotism as a moderating variable - Kristina Wada Betu; Susana Purnamasari Baso (Journal of Enterprise and Development (JED), 2023)
Purpose — The purpose of this study is to analyze the effects of tax rates and tax socialization on MSME tax compliance, as well as to investigate whether patriotism can act as a moderating variable.Method — The type of research is quantitative research with hypothesis testing. The population in this study consists of individual MSMEs in the city of Kupang. The study comprised 152 respondents. The analytical method used in this study is descriptive analysis. For this study, the analysis was conducted using SmartPLS 4 software. SEM-PLS analysis is performed through two stages, namely outer model analysis and inner model analysis.Result — This study examines the effects of tax rates, tax socialization, and patriotism on MSME tax compliance, with patriotism serving as a moderating variable. Data analysis and discussion of the results reveal that tax rates, tax socialization, and patriotism have a positive and significant impact on MSME tax compliance. However, the moderation effect of patriotism on the relationship between tax rates and tax socialization, and MSME tax compliance, is not proven.Contribution — This study contributes to the academic landscape by addressing the understudied realm of individual MSME tax compliance and advancing compliance theories through the examination of patriotism as a potential moderating factor.